Mapeamento e caracterização das mensagens que exigem ação do piloto ou do técnico de manutenção durante a energização de aeronaves - Chaves, Fabiana Fernandes (2021)
The aeronautical industry has grown rapidly in the last decades, connecting not only countries, but also people and cultures. In this sector a great challenge is to remain not only efficient, but with the constant technological advancement, increasingly safe. The strict reliability standards from testing to the assembly of the product and the demand for after-sales service guarantee this safety, not only for passengers, but also for the entire crew. This work aims to analyze some failure messages, which are presented on the pilot control screen, detected at the startup of the aircraft that when not corrected, cause maintenance actions performed by highly qualified professionals, generating possible flight delays. The analysis was performed using Python 3, to acquire the necessary information from the aircraft database, and the Microsoft Excel spreadsheet editor, to analyze the frequency of events and classify in descending order the messages with the highest appearances. After this statistical analysis, the most frequent messages are passed to the engineering teams, responsible for each aircraft system, for further studies on the causes of appearance of each message. This procedure allowed a significant reduction of messages, and 85.29% will be sent for testing and software updates.